2018
DOI: 10.1038/s41419-018-0956-4
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin attenuates detrimental effects of diabetes on the niche of mouse spermatogonial stem cells by maintaining Leydig cells

Abstract: Diabetes mellitus affects a large number of men of reproductive age and it usually leads to serious reproductive disorders. However, the underlying mechanisms and specific therapies still remain largely unknown. We observed Leydig cell loss in the testes of diabetic mice. Continuous high glycemic status of testes stimulated expression of Caspase12, Grp78, and Chop, the three ERS response factors; this might induce cell cycle arrest and apoptosis of Leydig cells in response to ERS. In these diabetic mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 68 publications
1
45
0
1
Order By: Relevance
“…The reduction in ERS by melatonin through activation of ERAD has been reported in several studies [ 24 26 ]. Consistent with this, the ERAD markers Hrd1, Vcp , and Os9 increased remarkably after treatment of cADMSCs with melatonin for 12h, while Hrd1 was inhibited by luzindole ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The reduction in ERS by melatonin through activation of ERAD has been reported in several studies [ 24 26 ]. Consistent with this, the ERAD markers Hrd1, Vcp , and Os9 increased remarkably after treatment of cADMSCs with melatonin for 12h, while Hrd1 was inhibited by luzindole ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Secondly, the C18-4 cells used in our study were an immortalized SSC line ( 29 ) which were characterized with typical SSC marker expression ( SI Appendix , Fig. S7 A and B ) ( 58 ) and had been extensively used for investigating self-renewal regulation of SSCs ( 59 61 ) and in vitro germline toxicity assessment ( 62 ); however, their competence for continued spermatogenesis was not proven. While other germline stem cells, such as mouse GS cells ( 63 ), would be a closer mimic of primary SSCs, the transgene delivery method (mainly through electroporation) and its relatively low efficiency limited large-scale biochemical analysis of them ( 64 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…MT has been shown to prevent environmental and drug-induced testicular damage due to its antioxidant properties (Galano, Castaneda-Arriaga, Perez-Gonzalez, Tan, & Reiter, 2016;Li et al, 2016;Mukherjee, Haldar, & Vishwas, 2015;Reiter et al, 2017). Moreover, MT may reduce the damage dealt with diabetic Leydig cells (Du, et al, 2018). Moreover, MT may reduce the damage dealt with diabetic Leydig cells (Du, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study (Zhang, Lv, Jia, & Huang, 2012) showed that MT could also effectively protect testicular tissues against the structural and functional damage caused by an HFD. Moreover, MT may reduce the damage dealt with diabetic Leydig cells (Du, et al, 2018). As testosterone replacement therapy has a number of side effects and risks (Cao & Kaufman, 2014), a more natural, safe treatment for infertility in obese males would be beneficial.…”
Section: Introductionmentioning
confidence: 99%